Lizard loopy: a secret potion....a world of adventure - Sparkes, Ali; Collins, Ross (illustrator) (Oxford, Oxford University Press, 2012)
Josh and Danny can't wait to try out Petty Potts's crazy new spray that will turn them into lizards! Soon, they're making the most of their amazing speed and agility by whizzing up a tree. But in no time they're in deep doo-doo, surrounded by bird poo and in serious danger of being swallowed whole by two moody owls.